Inflammatory Cytokines, but Not Dietary Patterns, Are Related to Somatic Symptoms of Depression in a Sample of Women - Hazeltine, Danielle Belden; Polokowski, Ashley Rose; Reigada, Laura Christine (Frontiers in Psychiatry, 2022)
Depression is a heterogenous disorder with both cognitive and somatic symptom dimensions that may differentially relate to systemic inflammation. Diet, which has the potential to modulate both inflammation levels and mood, is yet to be studied within the context of individual depression dimensions. This study examined the associations between inflammatory cytokines and dietary patterns with depressive symptom dimension profiles among a sample of women recruited in a non-clinical setting. Inflammatory cytokines (IL-6 and TNF-α), inflammatory diet (Diet Inflammatory Index; DII), and depressive symptoms (Beck Depression Inventory-II; BDI-II) were measured in 136 females (Mage = 22.01 ± 4.02, range 18 to 59 years). Multiple linear regressions were used to investigate the relationships between inflammatory cytokines and diet with self-reported cognitive, somatic, and total depressive symptoms, adjusting for demographic factors. Findings showed that increased somatic dimension scores were positively associated with IL-6 (ß = 0.273, p = 0.002) and TNF-α (ß = 0.215, p = 0.017), but not inflammatory diet (p = 0.300). Total BDI-II scores were only positively associated with IL-6 (ß = 0.221, p = 0.012), and cognitive dimension scores were not associated with any inflammation measures. These findings contribute to existing evidence that inflammatory cytokines are associated with the somatic symptoms of depression. Inflammatory diet index was not associated with depression measures.